The Motif of the Danube in Eminescian Lyrics: Array - Golovanova, Elena (Journal of Danubian Studies and Research, 2021)
The Danube is an integral part of Romanity. In the nineteenth century the Danube had become an obsession in the sense of its integration into the lyrical triad "Carpathian-Danubian-Pontic". In a natural way, Eminescu integrates the Danube motif among the others frequented with lyrical diligence. The specific marks of Eminescianism are found in the poetic visionarism, integrated in emblematic poems such as "Memento mori", "The 3rdLetter", or "Farewell". The lyrical instancetransposess the geographical detail into an integral part of a perception of the grand and transcendent.